EVIDENCE BASED CASED REPORT (EBCR) PENGARUH PIJAT BAYI TERHADAP KUALITAS TIDUR BAYI (Politeknik Kesehatan Kemenkes Bandung, 2022)
Background: Baby massage is a method that can provide comfort to the baby because it can help relax tense muscles so that the baby becomes calm and sleeps soundly. The benefits of pijat bayi are weight gain and growth, stamina, focus on the baby, sound baby sleep, bonding between mother and baby, and increased milk production. This happens when the baby is massaged by the parents themselves, the bond between the parents and the baby will be further enhanced. The closest family can be included in the pijat bayi to get closer to the emotional connection, for example fathers, grandmothers, grandfathers. The baby's instinct can respond to the mother's touch as an expression of love, protection and care. In addition to its benefits, pijat bayi can cause problems if not done properly. As a result of improper massage this can cause trauma or bruising to the skin and muscles, pain in babies. Purpose: The purpose of this evidence-based case report is to find out whether infant massage has an effect on infant sleep quality. Method:The search for this article was carried out using the e-database Pubmed and ScienceDirect. Result: Two articles published by Sri Wahyuni​​​​​​​​​​​​​​​​ and Siti Noorbaya et al. This article was taken according to the inclusion and exclusion criteria then critically reviewed. Conclusions: Baby massage has been proven to improve the quality of baby sleep